2007
DOI: 10.1007/s10562-007-9202-x
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of Cyclohexene on Platinum Nanoclusters on a Thin Film of Al2O3/NiAl(100)

Abstract: Using a scanning-tunneling microscope, reflection high-energy electron diffraction and photoelectron spectra with synchrotron radiation, we investigated the temperature dependence of the dehydrogenation of cyclohexene (C 6 H 10 ) adsorbed on Pt nanoclusters supported on an ultra-thin film of Al 2 O 3 /NiAl(100). The Pt clusters, grown by vapor deposition, are structurally ordered and exhibit a mean diameter 2.2 nm and height 0.4 nm. The progress of dehydrogenation was monitored through the temporal variation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…At elevated temperatures some benzene desorbs (if at high coverage) and the remainder dehydrogenates further via an intermediate with a 2:1 C/H ratio to eventually form graphitic carbon on Pt(111) . A similar dehydrogenation pathway has been reported for the adsorption of cyclohexene on platinum nanoparticles supported on thin-film Al 2 O 3 . The π-allyl species has also been observed during high pressure reactions of cyclohexene with Pt(111). , …”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…At elevated temperatures some benzene desorbs (if at high coverage) and the remainder dehydrogenates further via an intermediate with a 2:1 C/H ratio to eventually form graphitic carbon on Pt(111) . A similar dehydrogenation pathway has been reported for the adsorption of cyclohexene on platinum nanoparticles supported on thin-film Al 2 O 3 . The π-allyl species has also been observed during high pressure reactions of cyclohexene with Pt(111). , …”
Section: Introductionmentioning
confidence: 55%
“…They find the most stable adsorption site to be an hcp site, forming a triple-σ bonded species. However, experimental XPS C(1s) binding energies , and HREELS ,, suggest that the π-allyl has partially sp 2 character and, thus, at least partial π bonding to the platinum surface. However, Morin et al find the adsorption energy of the hcp triple-σ species and the bridge σπ species to differ by only 6 kJ/mol, within the uncertainty of their calculation.…”
Section: Discussionmentioning
confidence: 98%
“…Platinum nanomaterials play a key role in the production of gasoline, through their catalysis of reforming and isomerization processes used to create higher octane components for gasoline. Cyclic hydrocarbons such as cyclohexane and cyclohexene undergo platinum-catalyzed dehydrogenation reactions to form benzene, which is used to blend higher octane gasoline. , Extensive research into these reactions has revealed the effect of symmetry, particle size, and temperature on the performance of the Pt catalysts. , While platinum catalysts are normally less than 1.3 wt %, bimetallic Pt-based catalysts such as PtSn help to improve performance and decrease the Pt loading requirements. , …”
Section: Applications Of Pt and Pt-based Nanomaterialsmentioning
confidence: 99%
“…This Pt/Al 2 O 3 system attracts much research [10][11][12][13][14][15][16][17][18] because of its prospective application in important technologies, such as petroleum treatment, fuel cells and NO x reduction. [19][20][21][22][23][24][25] The Pt clusters, grown from vapor deposition on the Al 2 O 3 /NiAl(100), had mean diameter 2.2 nm and height 0.4 nm, and were shown to undergo a temperature-dependent oxidation, in the absence of a gaseous oxidizing agent. Upon the formation of Pt clusters on the oxide at 300 K, the electronic structure of the Al 2 O 3 thin film alters significantly: the Al 2p (Al ox 2p) and O 1s photoelectron signals from Al 2 O 3 shifted 0.4-0.5 eV toward smaller binding energy (BE), indicating a transfer of charge from the Pt clusters to the oxide, so that the Pt clusters become partially oxidized.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we investigated the interaction of Pt nanoclusters with a thin film of Al 2 O 3 grown on NiAl(100) at various temperatures, with surface-probe techniques including synchrotron-based photoelectron spectroscopy (PES), scanning tunneling microscopy (STM), and reflection high-energy electron diffraction (RHEED). This Pt/Al 2 O 3 system attracts much research because of its prospective application in important technologies, such as petroleum treatment, fuel cells and NO x reduction. The Pt clusters, grown from vapor deposition on the Al 2 O 3 /NiAl(100), had mean diameter 2.2 nm and height 0.4 nm, and were shown to undergo a temperature-dependent oxidation, in the absence of a gaseous oxidizing agent. Upon the formation of Pt clusters on the oxide at 300 K, the electronic structure of the Al 2 O 3 thin film alters significantly: the Al 2p (Al ox 2p) and O 1s photoelectron signals from Al 2 O 3 shifted 0.4−0.5 eV toward smaller binding energy (BE), indicating a transfer of charge from the Pt clusters to the oxide, so that the Pt clusters become partially oxidized.…”
Section: Introductionmentioning
confidence: 99%